Identifying the influences of nominal and real rigidities in aggregate price-setting behavior - Günter Coenen; Andrew T. Levin (European Central Bank (ECB), 2004)
We formulate a generalized price-setting framework that incorporates staggered contracts of multiple durations and that enables us to directly identify the influences of nominal vs. real rigidities. Using German macroeconomic data over the period 1975Q1 through 1998Q4 toestimate this framework, we find that the data is well-characterized by a truncated Calvostyle distribution with an average duration of about two quarters. We also find that new contracts exhibit very low sensitivity to marginal cost, corresponding to a relatively high degree of real rigidity. Finally, our results indicate that backward-looking behavior is not needed to explain the aggregate data, at least in an environment with a stable monetary policy regime and a transparent and credible inflation objective.
Keywords: E31; E52; 330; Inflation persistence; nominal rigidity; overlapping contracts; real rigidity; simulation-based indirect inference